2005
DOI: 10.1108/09544780510594207
|View full text |Cite
|
Sign up to set email alerts
|

Using machine learning to support quality management

Abstract: PurposeTo demonstrate the applicability of machine‐learning tools in quality management.Design/methodology/approachTwo popular machine‐learning approaches, decision tree induction and association rules mining, were applied on a set of 960 production case records. The accuracy of results was investigated using randomized experimentation and comprehensibility of rules was assessed by experts in the field.FindingsBoth machine‐learning approaches exhibited very good accuracy of results (average error was about 9 p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 14 publications
(15 reference statements)
0
14
0
1
Order By: Relevance
“…Tsironis (2015), Tsironis et al (2005) and Papazoglou (2008) reported several pitfalls of the use of the seven new QTs. Their application is governed by several bureaucratic obstacles.…”
Section: Rationalementioning
confidence: 99%
See 3 more Smart Citations
“…Tsironis (2015), Tsironis et al (2005) and Papazoglou (2008) reported several pitfalls of the use of the seven new QTs. Their application is governed by several bureaucratic obstacles.…”
Section: Rationalementioning
confidence: 99%
“…This reason has to do with the compatibility of the results of DMT (inference rules and patterns) with the type of information that is needed as an input in order to create them (Köksal et al , 2011; Kahraman and Yanik, 2016). Particularly, the qualitative orientation of the QT achieves a compatible combination with the DMT (Tsironis, 2015; Tsironis et al , 2005; Papazoglou, 2008).…”
Section: Rationalementioning
confidence: 99%
See 2 more Smart Citations
“…Πλεονεκτήματα του Στατιστικού Ελέγχου Ποιότητας είναι η στατιστική διερεύνηση της πορείας της διαδικασίας παραγωγής, η αποφυγή απόρριψης και επιδιόρθωσης, και η εξασφάλιση ομοιογενούς ποιότητας.Καταλυτικό παράγοντα τα επόμενα χρόνια στην εξέλιξη του Στατιστικού Ελέγχου Ποιότητας αναμένεται να παίξουν οι τεχνικές Μηχανικής Μάθησης, εμπλουτίζοντας τις ήδη υπάρχουσες μεθόδους και συμβάλλοντας στην ανάπτυξη ακόμα ισχυρότερων εργαλείων για τον έλεγχο ποιότητας (βλ. για παράδειγμα,Tsironis et al, 2005).Η και μάθηση χωρίς επίβλεψη (ή μάθηση από παρατήρηση) (Hastie et al, 2001) (Πίνακας 3.1).…”
unclassified